Lupus podocytopathy presenting as lupus cerebritis: a rare diagnostic challenge in a young female - Sheth, Geeta; Sabu, Manu S.; Sayed, Salman A.; Sarkate, Monica M.; Das , Saptadipa (International Journal of Advances in Medicine, 2025)
Lupus cerebritis is a serious complication usually seen in patients with lupus nephritis. However, lupus podocytopathy presenting as lupus cerebritis is extremely rare and, to the authors’ knowledge, has not been reported. We present the case of a 19-year-old female with no known comorbidities who presented with seizures, headache, and altered sensorium. Cerebrospinal fluid analysis showed lymphocytic pleocytosis, and brain imaging revealed diffuse encephalitis. She was initially treated as viral encephalitis, but subsequent serology confirmed systemic lupus erythematosus with high-titer ANA and positive nucleosome and histone antibodies. The diagnosis of lupus cerebritis was made, and she improved with high-dose corticosteroids and immunosuppressive therapy. Within days, she developed nephrotic-range proteinuria and hypoalbuminemia (1.8 g/dl). Kidney biopsy demonstrated diffuse podocyte foot process effacement without immune complex deposition, consistent with lupus podocytopathy. She was treated with corticosteroids, hydroxychloroquine, and mycophenolate mofetil, resulting in remission. This case highlights that lupus podocytopathy can rarely present with neurological symptoms, and timely diagnosis and treatment can lead to excellent outcomes.